Clustering and Visualising Documents using Word Embeddings - Reades, Jonathan; Williams, Jennie (The programming historian, 2023)
This lesson uses word embeddings and clustering algorithms in Python to identify groups of similar documents in a corpus of approximately 9,000 academic abstracts. It will teach you the basics of dimensionality reduction for extracting structure from a large corpus and how to evaluate your results.